Peningkatan Kemampuan Komunikasi Matematis dan Kebiasaan Berpikir Siswa Melalui Model Pembelajaran IMPROVE - Ayudiasari Anggriani; Ari Septian (IndoMath: Indonesia Mathematics Education, 2019)
The purpose of this study is to determine wether the improvement of students' mathematical communication skills using the IMPROVE learning model is better than the improvement of students' mathematical communication skills using the conventional method, and also to find out the students' thinking habits towards mathematics learning through the IMPROVE learning model. This research was conducted at SMPN 1 Bojongpicung grade VII of the 2018-2019 school year. The method used is a quasi experiment method with nonequivalent pretest-posttest control group design research. This research involved a sample of 64 students divided into two classes. One class as the experimental group that received learning with the IMPROVE learning model and then another one as the control group that was used the ordinary learning method. Sampling is done by purposive sampling technique. To get the data of the research results, the researcher used a mathematical communication ability test instrument and questionnaire for students' thinking habits. Data processing enhances students' mathematical communication skills using Mann Whitney, habitual data thinking students use the percentage of answers for each student. Based on data analysis, the improvement of students' mathematical communication skills using the IMPROVE learning model is better than increasing students' mathematical communication skills using conventional method, and students' thinking habits are positive towards the learning mathematics using the IMPROVE learning model.